Effects of wound infection on prognosis after laparoscopic abdominoperineal resection of rectal cancer - Huang, Wang; Wei, Zheng-qiang; Qiu, Yu-hao; Tang, Gang; Sun, Hao (Frontiers in Oncology, 2023)
Background: In two facilities in Chongqing, this research sought to retrospectively evaluate the effects of perineal wound infection on survival after laparoscopic-assisted abdominoperineal resection (LAPR) of rectal cancer. Methods: To obtain clinical information on patients who underwent LAPR between January 2013 and December 2021, we performed a multicenter cohort study. A total of 473 patients were enrolled: 314 in the non-infection group and 159 in the group with perineal infection. The general data, perioperative conditions and tumor outcomes between groups were analyzed. The infection rates, recurrence rates and survival rates of the two centers were compared. Results: Age, height, weight, BMI, preoperative complications, preoperative treatment and intraoperative conditions of patients in the LAPR infection group were not statistically significant. The percentage of males, typical postoperative hospital stay, length of initial postoperative therapy, and recurrence and metastasis rates were all considerably higher in the infection group than the non-infection group. Wound infection was an independent factor affecting tumor recurrence and metastasis after LAPR as well as an independent factor shortening patient survival time, according to multivariate analysis. The incidence of wound infection, the rate of recurrence, and the rate of mortality did not vary significantly across sites. Conclusion: Wound infection after LAPR increases the mean postoperative hospital stay, prolongs the time to first postoperative treatment, and decreases DFS and OS Wound infection after LAPR increased the postoperative hospital stay, affects postoperative adjuvant therapy, and decreased the disease-free survival and survival time. Therefore, decreasing the rate of LAPR wound infection is expected to shorten postoperative hospital stay, and prolong patient DFS and OS. Patients with postoperative infection may require intensive adjuvant therapy.